Identification and Characterization of Sources of Resistance to Peronospora variabilis in Quinoa - Álvaro Calderón-González; Javier Matías; Verónica Cruz; Leire Molinero-Ruiz; Sara Fondevilla (Agronomy, 2023)
Downy mildew, caused by Peronospora variabilis, is the most important quinoa disease worldwide. However, little is known about the resistance mechanisms acting against this disease. The study goals were to identify quinoa accessions showing resistance to P. variabilis under Spanish field conditions and to characterize the resistance mechanism involved. Towards these objectives, a total amount of 229 accessions of Chenopodium quinoa and one accession of each of the species Chenopodiun berlandieri subs. nutillae, Chenopodium ugandae, and Chenopodium opulifolium were screened for resistance to P. variabilis under field conditions in Córdoba, Spain, during two seasons. The response to P. variabilis in the accessions showed a continuous distribution ranging from complete resistance to high susceptibility. Fifteen resistant and one susceptible accessions were selected for further histological studies. Histological results showed that resistance to downy mildew in quinoa acts mainly at the stage of colony establishment. In resistant accessions, no colonies were formed or success in colony establishment was significantly reduced compared with the susceptible control. Hypersensitive response was associated with colony abortion in a number of the resistant accessions. This work is the first proof of hypersensitive reaction occurrence in quinoa as a response to P. variabilis.